Implementation of Information Technology in Agrotourism Promotion Policy: A Public Administration Perspective - Zulmasyhur, Zulmasyhur (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
The increasing significance of agrotourism in rural economic development has highlighted the critical role of promotional strategies, mainly through digital platforms. The focus on websites has revolutionized communication patterns and business operations in various sectors. However, there is still a significant gap in understanding the implementation of its strategies, particularly for agrotourism promotion. This study explores the strategic policies, utilization potentials, and operational capacities of website utilization in promoting agrotourism destinations. Then, using qualitative research methodology, this study examines how digital platforms can effectively serve as a tool for preparing, promoting, and disseminating information in the agrotourism sector. The study findings reveal that website management strategies by agrotourism operators significantly increase public awareness and enhance the visibility of tourist destinations. This study has important implications for agrotourism stakeholders, indicating that systematic website utilization can serve as a good marketing tool, facilitating improved communication between service providers and potential visitors while contributing to the overall development of rural tourism destinations. This study provides insights for policymakers and agrotourism managers in developing effective digital promotion strategies that align with modern tourist’s information-seeking behavior.